A multicenter phase II study of the cryptophycin analog LY355703 in patients with platinum-resistant ovarian cancer. Issue 1 (1st January 2006) - D'agostino, G.; Del Campo, J.; Mellado, B.; Izquierdo, M. A.; Minarik, T.; Cirri, L.; Marini, L.; Perez-Gracia, J. L.; Scambia, G.
Abstract : LY355703 is a synthetic product structurally related to the cryptophycin family isolated from the blue-green algae, which exerts a potent destabilization of microtubules during mitosis. This study was performed to determine the activity of LY355703 in patients with platinum-resistant advanced ovarian cancer and to characterize its toxicity profile. Twenty-six patients were enrolled in this study. Resistant disease was defined as a platinum-free interval of <6 months from primary treatment or rechallenge. LY355703 (1.5 mg/m 2 ) was administered intravenously on days 1 and 8, every 3 weeks, infused over 2 h. From 24 patients evaluable for response, three partial responses (12.5%) and seven disease stabilizations were registered (29.2%), for an overall clinical benefit of 41.7%. Fourteen patients (58.3%) experienced a progression of the disease during treatment. Among the 25 patients evaluable for toxicity, two episodes of grade 3 anemia (8%); one, grade 3 thrombocytopenia (4%); one, grade 4 elevation of creatinine (4%); and one, grade 3 hyperbilirubinemia (4%) were reported. LY355703 has a modest activity in patients with platinum-resistant advanced ovarian cancer. Nevertheless, the considerable rate of disease stabilization in the absence of serious adverse events in this poor-prognosis study population suggests that this novel cryptophycin may deserve further investigation in this setting.